Inclusion of human immunodeficiency virus Type 2 (HIV‐2) in a multiplex transcription‐mediated amplification assay does not affect detection of HIV‐1 and hepatitis B and C virus genotypes: a multicenter performance evaluation study. Issue 9 (23rd June 2015) - Grabarczyk, Piotr; Koppelman, Marco; Boland, Fiona; Sauleda, Silvia; Fabra, Cécile; Cambie, Giuseppe; Kopacz, Aneta; O'Riordan, Karen; van Drimmelen, Harry; O'Riordan, Joan; Lelie, Nico
Abstract : BACKGROUND: The Ultrio Elite assay (Hologic/Grifols) runs on the Panther blood screening system and is comparable to the Ultrio Plus assay apart from the addition of oligonucleotides for human immunodeficiency virus Type 2 (HIV‐2) detection. In this multicenter evaluation study the analytical sensitivity and genotype detection efficiency of the two assay versions were compared. STUDY DESIGN AND METHODS: The analytical sensitivity and genotype detection efficiency were analyzed by replicate (18‐303) testing of 27 hepatitis B virus (HBV), hepatitis C virus (HCV), HIV‐1, and HIV‐2 standard dilution panels calibrated in international units (IUs) and copies/mL. A wider range of subgenotypes was tested at 25 copies/mL. Specificity was evaluated in 30, 756 donor samples. RESULTS: The 95% lower limits of detection (LODs) in Ultrio Elite assay on WHO standards were 4.6, 7.3, 23.5, and 23.3 IU/mL for HBV, HCV, HIV‐1, and HIV‐2, respectively, and ranged from 13 to 44, 7 to 23, 6 to 15, and 9 copies/mL on genotype panels of the respective viruses. Comparable LODs had been previously found on the same panels with the Ultrio Plus assay. The specificity was 99.95% on initial test and 100% in the repeat test algorithm. CONCLUSION: The change in the oligonucleotide design of the Ultrio Elite assay to enable HIV‐2 detection has not affected the analytical sensitivity for the other viruses regardless of the genotype. Genotype reference panels are instrumental to compare the sensitivity of nucleic acid test assay versions and could serve as an alternative to seroconversion panels.